KEPEMIMPINAN EKOLOGIS KEPALA SEKOLAH DALAM PEMBENTUKAN SEKOLAH BERBUDAYA LINGKUNGAN - Noer Rizki Lailatul Azmi; Ahmad Yusuf Sobri; Ahmad Nurabadi (Universitas Negeri Malang, 2018)
Abstract: This study aimed to describe ecological leadership as a form of implementation of principal leadership who had environmental concern towards the conservation and preservation of living environment function, which was implemented in the establishment of environmental cultured school. This study was done through qualitative approach by employing case study research design. The data collection was done through interview, observation, and documentation. The data analysis was done through series of data reduction, data display, and conclusion drawing. The results showed that the impacts of ecological leadership of the principal in environmental school cultured establishment were the establishment of environmental concerned attitude, clean and healthy life style, ecological school environment, and school achievement in environmental field.Keywords: ecological leadership, environmental cultured school, ecological environment Abstrak: Penelitian ini bertujuan untuk mendeskripsikan kepemimpinan ekologis sebagai bentuk kepemimpinan kepala sekolah yang memiliki kepedulian lingkungan terhadap penyelamatan dan pelestarian fungsi lingkungan hidup yang diimplementasikan dalam pembentukan sekolah berbudaya lingkungan. Penelitian ini menggunakan pendekatan kualitatif dengan jenis studi kasus. Pengumpulan data menggunakan metode wawancara, observasi, dan dokumentasi. Analisis data dilakukan dengan serangkaian reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian memperlihatkan bahwa dampak kepemimpinan ekologis kepala sekolah dalam pembentukan sekolah berbudaya lingkungan adalah terbentuknya sikap peduli lingkungan, pola hidup bersih dan sehat, lingkungan sekolah yang ekologis, dan prestasi sekolah di bidang lingkungan.Kata kunci: kepemimpinan ekologis, sekolah berbudaya lingkungan, lingkungan ekologis